Elderly Took Preventive Role in Facing Flood Threat in Mountain Slope Area in Jember, East Java - Kinanthi, Citra Anggun; Noveyani, Adistha Eka; Hakiim, Arsyzilma (Universitas Pancasakti Tegal, 2023)
Tempurejo Subdistrict is a cantilever for Meru Betiri National Park in the southern part of Jember Regency. In every rainy season, it is certain that several villages in this sub-district are always flooded. Hence the flood disaster preparedness education becomes very necessary. Knowledge and understanding of disaster preparedness must be known to anticipate disaster situations quickly and accurately. The purpose of this activity is to provide education to the community regarding before, during, and after a disaster management. In addition, to maintain the sustainability of the community, a sub-district disaster preparedness team was formed and continuously assisted. The activity was held in October 2021 with the target of Karang Wreda Abiyoso members. Counselling materials were related to the flood disaster preparedness and the risk disease of post-flood through videos and the disaster response pocketbooks. As the result, there was an increasing of the post-test than the pre-test, so this counselling is effective in increasing the knowledge of the participants. Furthermore, disaster response training was carried out and one of the training courses was preparing a disaster preparedness bag. As a result, 9 out of 10 participants were able to simulate the preparation of a disaster preparedness bag within the allotted time. Furthermore, continuous assistance was carried out through WhatsApp Group. This team is expected to be able to disseminate disaster preparedness knowledge to local residents and increase understanding regarding appropriate disaster preparedness in their area.